When Facebook Becomes a Part of the Self: How Do Motives for Using Facebook Influence Privacy Management? - Kang, Hyunjin; Shin, Wonsun (Frontiers in Psychology, 2021)
This study examines how three different motivations for using an SNS (i.e., self-expression, belonging, and memory archiving) influence multi-facets of privacy boundary management on the platform mediated by self-extension to it. In recognition of the fact that information management on SNSs often goes beyond the “disclosure-withdrawal” dichotomy, the study investigates the relationships between the three SNS motives and privacy boundary management strategies (i.e., collective boundary and boundary turbulence management). An online survey with Facebook users (N = 305) finds that the three Facebook motivations are positively correlated to users’ self-extension to Facebook. The motivations for using Facebook are positively associated with the management of different layers of privacy boundaries (i.e., basic, sensitive, and highly sensitive) when Facebook self-extension is mediated. In addition, the three motives have indirect associations with potential boundary turbulence management mediated by Facebook self-extension. Extending the classic idea that privacy is deeply rooted in the self, the study demonstrates that perceiving an SNS as part of the self-system constitutes a significant underlying psychological factor that explains the linkage between motives for using SNSs and privacy management.